2017
DOI: 10.5194/se-8-1153-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spent mushroom compost application on the physicochemical properties of a degraded soil

Abstract: Abstract. Under field and laboratory conditions, the application of organic amendments has generally shown an improvement in soil physicochemical properties. Here, spent mushroom compost (SMC) is proposed as a suitable organic amendment for soil structure restoration. Our study assessed the impact of SMC on the physicochemical properties of a weak-structured and physically degraded soil. The approach involved the establishment of a pot experiment with SMC applications into soil (control, 0.5, 1, 2, 4 and 8 %).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Organic amendments have profound influences on soil's physical properties. Several studies revealed that the application of organic manures decreased the bulk density [33,[147][148][149] and penetration resistance [149], whereas it increased the aggregate stability [150][151][152], total porosity [152,153], hydraulic conductivity, and permeability [150,154]. Soil organic matter is an important attribute of soil quality and aggregate stability, which is influenced by the inherent properties of soil such as soil type and texture [155,156] as well as agronomic factors such as management, inputs, and nature of the organic matter [157].…”
Section: Reclamation With Organic Amendmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic amendments have profound influences on soil's physical properties. Several studies revealed that the application of organic manures decreased the bulk density [33,[147][148][149] and penetration resistance [149], whereas it increased the aggregate stability [150][151][152], total porosity [152,153], hydraulic conductivity, and permeability [150,154]. Soil organic matter is an important attribute of soil quality and aggregate stability, which is influenced by the inherent properties of soil such as soil type and texture [155,156] as well as agronomic factors such as management, inputs, and nature of the organic matter [157].…”
Section: Reclamation With Organic Amendmentsmentioning
confidence: 99%
“…The incorporation of organic amendments had also been found to improve chemical properties such as decrease in pH [27,147,158,159], EC [27,158,160], ESP [33,158], and SAR [27], while there is an increase in the soil organic matter [153,161], organic carbon [132,147,151,152,159,[162][163][164], CEC [152,162], total nutrients [32,151,161], and available nutrients [32,132,147,149,153,159,162,164,165].…”
Section: Sources Of Organic Amendmentsmentioning
confidence: 99%
“…As an organic manure, its application to sandy soils and soils under long-term tillage can help to improve soil structure and reduce soil erosion and nutrient loss (Hackett et al, 2010;Spink et al, 2010;Regan et al, 2012;Hackett, 2015;Gümüs & Seker, 2017). Temperature and moisture content have a significant effect on microbial activity and the enzymatic degradation of SMS during storage, and organic substrates will continue to compost and break down over time (Liang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Spent mushroom substrate as a fertiliser is a good source of nitrogen (N), phosphorus (P), potassium (K) as well as other minerals (calcium (Ca), magnesium (Mg), iron (Fe), manganese (Mn), zinc (Zn) and copper (Cu)); however, it does not contain sufficient N to provide the total N requirement for optimum plant growth (Stewart et al, 1998;Uzun, 2004;Walsh, 2013) and, furthermore, only a proportion of the total N is available for uptake by plants in the year of use (Hackett, 2015). The main advantages of SMS as a fertiliser are the slow release of nutrients, an increase in soil organic matter and the improvement of soil structure and health, attributes which are visible in the years following the initial application (Curtin & Mullen, 2007;Gümüs & Seker, 2017). Agricultural sustainability requires good soil management and the preservation of soil organic matter, and one way of achieving this is to recycle organic products, such as SMS, by incorporation into agricultural land (White et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the effect of the organic matter content on the fertility of soils (Loveland &Webb, 2003 andPan et al, 2009). Gümüs and seker (2015) reported that, humic acid applications can improve chemical and physical properties of soil such as EC, soil organic carbon, total nitrogen, modulus of rupture and aggregate stability. Sangeetha et al (2006), reported that, the humic Substances, the major component of soil organic matter has both direct and indirect effects on plant growth.…”
Section: Effect Of Soil Treatment With Different Rates Of Humic Acid ...mentioning
confidence: 99%